Study of Renal Function and Serum Electrolyte in Type - 2 DM - Sitholay, Pooja A.; Agnihotri, Dr. Madhuri A.; Ambad, Ranjit S. (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - To find out the level of serum Creatinine, serum uric acid, blood urea and serum electrolytes in Type-2 DM patients compare to normal healthy control group. Method: - A total number of 278 subjects were selected for study at CCM Medical College Hospital Durg. In which 178 subjects are suffering from type-2 DM average range of 30 to 65 years. 100 subjects age, sex matched was selected for control group. Controls were clinically and physically normal and healthy. Result: - The Mean±SD of serum sodium in diabetic group was 134.72±6.02mmol/L, 133.82±4.98 in male and female respectively and in control group was 139.16±2.83mmol/L. The Mean±SD of serum potassium in diabetic group was 6.28±1.07 mmol/L in male and 5.98±1.02 in female mmol/L and in control group was 4.62±0.46 mmol/L. The Mean±SD of serum calcium in diabetic group was 10.05±0.79 mg/dl in male and 9.95±0.69 mg/dl in female and in control group was 9.44±0.48 mg/dl. The present study shows that the activity of blood urea, serum creatinine and uric acid was highly significantly increased found in type-2 DM patients compare to normal healthy group. The activity was 42 ± 19 mg/dl, 2.92 ± 2.43 mg/dl, 12.26 ± 7.81 mg/dl in male and in female it was 39 ± 26 mg/dl, 2.26 ± 2.08 mg/dl and 10.96 ± 6.37 mg/dl and 22 ± 7.48 mg/dl, 0.83 ± 0.31 mg/dl and 5.26 ± 2.84 mg/dl respectively Conclusion: - This study shows highly significant alterations in Blood Urea, serum creatinine, serum uric acid, Serum Sodium, Serum Potassium and Serum Calcium levels in patients with type-2 DM suggesting renal damage. Screening tests for the complications of diabetes mellitus are strongly recommended at the time of diagnosis not only for early detection of DM but also to prevent the progression to end stage renal disease. In diabetes mellitus, electrolyte derangement prevails, so routine measurement of serum electrolyte and renal function could not be avoided in type-2 DM patients. Electrolyte imbalance occur even with normal renal function, however the frequency of electrolyte derangement is more with deterioration of the renal function in diabetes mellitus patients. In view of the fact that the present study comprised of a small group of patients, further studies with more number of patients may be required to evaluate our observations.